2015
DOI: 10.1159/000370309
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Models of Perinatal Infection

Abstract: One of the central, unanswered questions in perinatology is why preterm infants continue to have such poor long-term neurodevelopmental, cognitive and learning outcomes, even though severe brain injury is now rare. There is now strong clinical evidence that one factor underlying disability may be infection, as well as nonspecific inflammation, during fetal and early postnatal life. In this review, we examine the experimental evidence linking both acute and chronic infection/inflammation with perinatal brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 136 publications
(152 reference statements)
2
36
0
Order By: Relevance
“…Studies on LPS-sensitised HI injury have demonstrated microglia to be both more numerous and in a more activated state around the site of the lesion [18,45,46] . The sensitising effect of LPS on the immature brain has been attributed to the number of activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on LPS-sensitised HI injury have demonstrated microglia to be both more numerous and in a more activated state around the site of the lesion [18,45,46] . The sensitising effect of LPS on the immature brain has been attributed to the number of activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypoxia ischaemia has been modeled extensively in mice and rats (reviewed in Hagberg et al, 2002; van der Worp et al, 2007; Yager and Ashwal, 2009; Dean et al, 2015), with a minority of researchers also studying larger animals such as pigs, sheep (reviewed in Roohey et al, 1997; Dean et al, 2015) or primates (Fahn et al, 1979; Volpe, 2012). Models intending to replicate the clinical symptoms of neonatal human HI can be roughly divided into the four categories discussed below.…”
Section: Evaluation Of Available Animal Models Of Neonatal Hypoxia Ismentioning
confidence: 99%
“…(B) The general method with specifications taken from the pool of papers summarized in Supplementary Table 1. (C) The range of inflammatory models reviewed in Dean et al (2015).…”
Section: Evaluation Of Available Animal Models Of Neonatal Hypoxia Ismentioning
confidence: 99%
See 1 more Smart Citation
“…It is now recognized that the etiology of preterm brain injury is likely multifactorial. While HI is likely to be important, there is now compelling evidence that exposure to infection and secondary inflammation, both before and after birth, is highly associated with preterm brain injury and deficits in neuronal architecture and function in later life [2,3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%